2022
DOI: 10.3389/fpubh.2022.960627
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of oral rehydration salt utilization in diarrhea hot spot regions of Ethiopia and its associated factors among under-five children: A multilevel analysis based on Bayesian approach

Abstract: BackgroundDiarrhea leads the children to severe dehydration or death as a result of the loss of water and electrolytes (namely, potassium, chloride, sodium, and bicarbonate). To compensate for the losses, ORS is given to children who experienced diarrhea.ObjectiveTo estimate the magnitude of ORS utilization in diarrhea hotspot regions of Ethiopia and to assess its associated factors among under-five children.MethodsTo conduct this study, we used the 2016 Ethiopian demographic and health survey data. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Our study mentioned that media exposure was one of the factors associated with diarrhoeal treatment using ORS with zinc. This finding is in line with studies conducted in India,29 Bangladesh,37 Ghana38 and Ethiopia 25 34. This may be due to the media’s important role in increasing the mother’s or caregiver’s understanding and awareness of the best ways to treat diarrhoea in children 37…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our study mentioned that media exposure was one of the factors associated with diarrhoeal treatment using ORS with zinc. This finding is in line with studies conducted in India,29 Bangladesh,37 Ghana38 and Ethiopia 25 34. This may be due to the media’s important role in increasing the mother’s or caregiver’s understanding and awareness of the best ways to treat diarrhoea in children 37…”
Section: Discussionsupporting
confidence: 85%
“…The possible reason for this finding is older mothers were more likely than younger mothers to be knowledgeable about paediatric diarrhoea and how to treat it, younger mothers do not have as much exposure as older mothers about child diarrhoea and its management as maternal age can have impact on their knowledge about and how to treat it 27. This study found that maternal educational status was associated with the usage of ORS with zinc to treat under-5 diarrhoeal disease and this finding is supported by studies conducted in Pakistan,28 India,29 Nigeria,23 Cameron,30 Kenya31 and Ethiopia 21 25 32–34. This may be because educated women are more likely to take sick children to the medical facility and a woman with education is more likely than a mother without education to take her ill kid for follow-up as well as to take the ordered medication as per recommended.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations